2020
DOI: 10.1016/j.amsu.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Caution against precaution: A case report on silent hypoxia in COVID-19

Abstract: Introduction Silent hypoxia is an entity that has been described in patients diagnosed with COVID-19. It is typically described as objective hypoxia in the absence of proportional respiratory distress. The physiological basis for this phenomenon is controversial, and its prognostic value is unclear. We present a case below, of a 66-year-old female presenting with severe hypoxia that was managed without mechanical ventilation. Presentation of case A 66 year old female wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…There was a global increase in the reported infection rate and mortality [ 3 , 12 , 13 ]. However, literature reported many patients with COVID-19 presenting with silent hypoxia [ [14] , [15] , [16] ]. It is important to know the risk factors and the causes contributing to the presentation of silent hypoxia in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…There was a global increase in the reported infection rate and mortality [ 3 , 12 , 13 ]. However, literature reported many patients with COVID-19 presenting with silent hypoxia [ [14] , [15] , [16] ]. It is important to know the risk factors and the causes contributing to the presentation of silent hypoxia in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…He did not require ventilator support [ 8 ]. Lari et al reported another case of a 66-year-old patient who had silent hypoxemia who eventually needed high flow oxygen therapy and NIV [ 9 ]. Similar to our first patient, this patient had also shown multiple episodes of silent hypoxemia at the time of weaning from oxygen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are few case reports describing the perplexing entity -'silent hypoxia', there are a handful of cohort studies which have described the demographic, clinical and laboratory findings in such patients. 10,19,20 . Brouqui P et al 4 in their retrospective study, analyzed data from March 3rd to April 27 th , 2020 using dyspnea status, oxygen saturation, blood gas analysis, and low dose computed tomography scan reports.…”
Section: Discussionmentioning
confidence: 99%